CD137L-DCs, Potent Immune-Stimulators—History, Characteristics, and Perspectives - Zeng, Qun; Zhou, Yubin; Schwarz, Herbert (Frontiers in Immunology, 2019)
Dendritic cell (DC)-based immunotherapies are being explored for over 20 years and found to be very safe. Most often, granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-4 (IL-4)-induced monocyte-derived DCs (moDCs) are being used which have demonstrated some life-prolonging benefit to patients of multiple tumors. However, the limited clinical response and efficacy call for the development of more potent DCs. CD137L-DC may meet this demand. CD137L-DCs are a novel type of monocyte-derived inflammatory DCs that are induced by CD137 ligand (CD137L) agonists. CD137L is expressed on the surface of antigen presenting cells, including monocytes, and signalling of CD137L into monocytes induces their differentiation to CD137L-DCs. CD137L-DCs preferentially induce type 1 T helper (Th1) cell polarization and strong type 1 CD8+ T cell (Tc1) responses against tumor-associated viral antigens. The in vitro T cell-stimulatory capacity of CD137L-DCs is superior to that of conventional moDCs. The transcriptomic profile of CD137L-DC is highly similar to that of in vivo DCs at sites of inflammation. The strict activation-dependence of CD137 expression and its restricted expression on activated T cells, NK cells and vascular endothelial cells at inflammatory sites make CD137 an ideally suited signal for the induction of monocyte-derived inflammatory DCs in vivo. These findings and their potency encouraged a phase I clinical trial of CD137L-DCs against Epstein-Barr virus-associated nasopharyngeal carcinoma. In this review, we introduce and summarize the history, the characteristics, and the transcriptional profile of CD137L-DC, and discuss the potential development and applications of CD137L-DC.